DOES THE ATTACHMENT BETWEEN A FATHER AND HIS CHILD BOOST ADOLESCENTS' SELF-ESTEEM IN MINANGKABAU? - Rahmadianti Aulia; Irsyad Shabri (Universitas Negeri Padang, 2024)
Adolescents with low self-esteem often exhibit negative social behavior. Teens with lower self-esteem are believed to be those who do not have a strong bond with or are not linked to their fathers. This study aims to investigate how parenting practices, in particular father-child connection, impact the self-esteem of teenagers in the Minangkabau community. The study involved 166 teens from the ethnic group of Minangkabau. The Self Esteem Scale and the IPPA-R for Children were used to assess the variables, and simple linear regression was used to analyze the data using SPSS 25. The results show that father-child bonding in parenting has a substantial impact on teenagers' self-esteem in Minangkabau.